Novel 5-Substituted Oxindole Derivatives as Bruton's Tyrosine Kinase Inhibitors: Design, Synthesis, Docking, Molecular Dynamics Simulation, and Biological Evaluation - Velavalapalli, Vani Madhuri; Maddipati, Venkatanarayana Chowdary; Gurská, Soňa; Annadurai, Narendran; Lišková, Barbora; Katari, Naresh Kumar; Džubák, Petr; Hajdúch, Marián; Das, Viswanath; Gundla, Rambabu (ACS omega, 2024)
Bruton's tyrosine kinase (BTK) is a non-RTK cytoplasmic kinase predominantly expressed by hemopoietic lineages, particularly B-cells. A new oxindole-based focused library was designed to identify potent compounds targeting the BTK protein as anticancer agents. This study used rational approaches like structure-based pharmacophore modeling, docking, and ADME properties to select compounds. Molecular dynamics simulations carried out at 20 ns supported the stability of compound 9g within the binding pocket. All the compounds were synthesized and subjected to biological screening on two BTK-expressing cancer cell lines, RAMOS and K562; six non-BTK cancer cell lines, A549, HCT116 (parental and p53-/-), U2OS, JURKAT, and CCRF-CEM; and two non-malignant fibroblast lines, BJ and MRC-5. This study resulted in the identification of four new compounds, 9b, 9f, 9g, and 9h, possessing free binding energies of -10.8, -11.1, -11.3, and -10.8 kcal/mol, respectively, and displaying selective cytotoxicity against BTK-high RAMOS cells. Further analysis demonstrated the antiproliferative activity of 9h in RAMOS cells through selective inhibition of pBTK (Tyr223) without affecting Lyn and Syk, upstream proteins in the BCR signaling pathway. In conclusion, we identified a promising oxindole derivative (9h) that shows specificity in modulating BTK signaling pathways.